Police Training for Managing Crime: With Special Reference to the Crime Data Management System of Bangladesh Police - Chowdhury, Saber Ahmed (Social Science Review, 2023)
Initiations of the Crime Data Management System (CDMS) have led e-policing to a higher level of accuracy. The purpose of this study is to explore the existing training on CDMS, assess the training needed on CDMS, and recommend some ways forward. This study follows the mixed methodology where the primary data were collected by using surveys, key informant interviews (KIIs), and FGDs. This study reveals that since its initiation in 2005, CDMS has been working to depict case information, investigation reports, and crime analysis. In 2010, this system introduced online medium, and the Police Headquarters took over total control from the Crime Investigation Department (CID). Gradually in 2015, the Dhaka Metropolitan Police (DMP) introduced this system and in 2016, this system has been used at all police stations throughout the country. Moreover, this study also finds that from 2009 to 2020 more than half of the police officials did not receive any training on CDMS. The training receivers express their dissatisfaction with its short duration, and the aged and newly promoted officers remain vulnerable due to the partial training system. Additionally, police officials working in local thanas remain largely untrained and they also need to use this software on a regular basis. Social Science Review, Vol. 40(1), Jun 2023 Page 73-88